2015
DOI: 10.1002/jsc.2006
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Alternate Framework for Assessing Microfinance Programs’ Contribution to Development: An Empirical Study in Tamil Nadu, India

Abstract: Microfinance institutions can enhance their contribution to financial inclusion promotion by expanding their suite of financial services, participating in a credit bureau, and providing portability of accounts, greater flexibility in operation, and financial literacy training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…More specifically, we found that organizations are co‐creating microfinance strategies by partnering with technology providers and using crowdfunding, efficient information systems, mobile banking, and credit scoring (Ashta, 2012). Moreover, a multi‐product strategy is being used to include not only other financial services, but also nonfinancial services in order to provide a competitive advantage (Biosca, Lenton, & Mosley, 2014; Shankar, 2015).…”
Section: Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we found that organizations are co‐creating microfinance strategies by partnering with technology providers and using crowdfunding, efficient information systems, mobile banking, and credit scoring (Ashta, 2012). Moreover, a multi‐product strategy is being used to include not only other financial services, but also nonfinancial services in order to provide a competitive advantage (Biosca, Lenton, & Mosley, 2014; Shankar, 2015).…”
Section: Research Directionsmentioning
confidence: 99%
“…Microfinance institutional development has been influenced by global pressures, interinstitutional contradictions, and intrainstitutional conflicts in logics (Ashta, 2019). The regulatory support (Britzelmaier, Kraus, & Xu, 2013), the control of corruption, the need for competition, and the use of rating agencies (Halouani & Boujelbène, 2015), credit bureaus (Shankar, 2015), or even “mystery shopping” (Chan & Lin, 2015) can all help in the supervision and development of microfinance organizations. However, inappropriate regulation can push microcredit organizations to increase outreach and inclusion but with a purely commercial logic (Khachatryan & Avetisyan, 2017).…”
Section: Research Directionsmentioning
confidence: 99%
“…In Tripura, Bandhan MFI (now operating as a bank) is the known MFI that offers financial services in the nontribal region through JLGs. High financial exclusion is also attributed to a lack of FC (Bickel & Mehwald, 2014; Blake & de Jong, 2008; Shankar, 2015). These researchers recognize that FC enhancement is an essential enabler for advancing FI.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Many households still access credit from individual moneylenders even if it is at a high cost, to avoid nonprice barriers (such as attending group meetings and making standardized loan repayment) (National Sample Survey Organisation [NSSO], 2014; Parekh & Ashta, 2018; Ramadorai, 2017). Their exclusion from formal banking and formal MF systems is not only due to the remoteness of their localities and the hilly terrain which makes accessing these services more challenging but also due to the lack of financial capability (FC) of the households in terms of knowledge about such programs, attitudes toward joining those programs, and poor management of their money and resources (Blake & de Jong, 2008; Shankar, 2015). In technical terms, FCs are the abilities of a person or a household to act, that is converting their internal abilities (in the form of assets, goods, income, education, knowledge, skills, and attitude) and external resources (such as physical infrastructures like financial institutions) into financial behavior (actions).…”
Section: Introductionmentioning
confidence: 99%
“…A study in India found that once an individual gains access to microfinance, three kinds of outcomes are possible (Shankar 2015). The first kind of outcome is in the case of MFI borrowers who utilize their loans primarily for their business activity and whose businesses generate sufficient margins after payment of principal and interest.…”
Section: Introductionmentioning
confidence: 99%